2020
DOI: 10.3847/1538-4357/aba518
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Genealogy: Identifying Hierarchical Mergers with Gravitational Waves

Abstract: In dense stellar environments, the merger products of binary black hole mergers may undergo additional mergers. These hierarchical mergers are naturally expected to have higher masses than the first generation of black holes made from stars. The components of hierarchical mergers are expected to have significant characteristic spins, imprinted by the orbital angular momentum of the previous mergers. However, since the population properties of first-generation black holes are uncertain, it is difficult to know … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 114 publications
8
96
0
Order By: Relevance
“…12 16 ( ) rate. It may also be possible to fit the maximum black hole mass below the gap assuming the population contains both isolated binaries and hierarchical mergers without needing to subtract the hierarchical mergers (Kimball et al 2020) Also, if a channel that produces black holes in the mass gap is rare, we may still be able to determine the location of the mass gap for the more dominant channel.…”
Section: Discussionmentioning
confidence: 99%
“…12 16 ( ) rate. It may also be possible to fit the maximum black hole mass below the gap assuming the population contains both isolated binaries and hierarchical mergers without needing to subtract the hierarchical mergers (Kimball et al 2020) Also, if a channel that produces black holes in the mass gap is rare, we may still be able to determine the location of the mass gap for the more dominant channel.…”
Section: Discussionmentioning
confidence: 99%
“…[32,68] for recent Bayesian analyses using spin in the PBH context and Ref. [69] for a Bayesian study including a zero-spin black hole population, which could be considered a simplified proxy for a PBH model.…”
Section: B Ligo Empirical Merger Modelsmentioning
confidence: 99%
“…However, recent works by Rodriguez et al (2020) and Gerosa et al (2020) have shown that the relative fraction of low-mass-ratio merger events can be enhanced by second-and third-generation mergers in dynamical environments, producing GW190412-like events as a result, though analysis by Kimball et al (2020) casts doubt on the hierarchical merger scenario for GW190412. Due to the efficiency of mass segregation, the remnant of a previous merger is expected to be twice as massive as the 1G BHs in the cluster (see also Samsing & Hotokezaka 2020).…”
Section: Massesmentioning
confidence: 99%